ANALISIS ANGKUTAN SEDIMEN DASAR (BED LOAD) PADA SALURAN IRIGASI MATARAM YOGYAKARTA - Anggi Hermawan; Erwin Nur Afiato (TEKNISIA, 2021)
In the last decade, the problem that has occurred in the Yogyakarta Mataram irrigation channel is the occurrence of sedimentation in the channel. This has an impact on reducing the cross-sectional discharge capacity of the canal and resulting in the supply of irrigation discharge to agricultural areas to be not optimal, so that agricultural productivity in the Mataram Irrigation Area will also not be optimal. The sediment transport (bed load) that occurs in an open channel can be approached using the empirical equation, including the Einstein, Meyer - Peter Muller and Frijlink equations. Sediment transport events that occur in the channel are stated based on the magnitude of the flow shear stress which exceeds the critical shear stress of the sediment particles. The quantity of sediment transport in the channel is stated on the logarithmic curve of the relationship between the froude number (fr) to the sediment transports (qb). The Curve  explains that the increase in the froude number (fr) that occurs on each section of the channel  will be directly proportional to the increase in the quantity of transport sediment (qb). The largest sediment transport occurred at the site of the Gambang and Nambongan channel section with a prediction of sediment transport of 3.57 m3/day and 3.67 m3/day, respectively. Thus, the potential for sediment transport that will settle in the downstream area is 3.67 m3/day.